Employee Capital Plans as an Instrument of Mobilising Additional Pension Savings in Poland - Jedynak, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The study examines employee capital plans (ECP). The main aim of the research is to assess the ability of ECPs to mobilise voluntary retirement savings. It conducts a meta-analysis on the results of other studies, examining four groups of factors that influence savings decisions: financial incentives, behavioural factors, financial education and social marketing. The comparison of these factors to the ECP system leads to the conclusion that they deservedly stress the behavioural factors, and within financial incentives they rightly focus on subsidies for savings. Furthermore, it is noted that financial education and social marketing are not included ECPs. The study found that, thanks to their combination of behavioural and financial factors, ECPs will increase the pension savings in Poland, but the scale of this impact on the savings rate and the universality of savings remains an open question.